Synthesis of asymmetrically substituted scyllo-inositol. Issue 30 (27th July 2016) - Rodriguez, Jacob; Walczak, Maciej A.
Graphical abstract: Highlights: scyllo -Inositol is a rare member of the inositol family and no asymmetric synthesis has been reported. Starting from inexpensived -glucose, stereoselective Ferrier-II carbocyclization afforded the myo -inositol core. The configuration of the final product was then adjusted in a two-step conversion of myo -inositol to scyllo -inositol. Abstract: scyllo -Inositol, a rare member of the inositol family, is present in axinelloside A, a marine metabolite with interesting inhibitory activity against human telomerase. Here, we present a concise synthesis of asymmetrically substituted scyllo -inositol starting from inexpensived -glucose. Our synthetic approach capitalizes on Ferrier rearrangement of vinyl acetate and stereoselective reduction of the resultant ketone to establish the scyllo -inositol core. The protocol provides access to large quantities of scyllo -inositol in 10 steps from commercially available materials.